Literature Review: Correlation of decreased glomerular filtration rate to malnutrition risk in pre-dialysis chronic kidney disease patients - Yenny Darmawaty Pangaribuan; Inggita Kusumastuty (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Chronic kidney disease (CKD) is a condition characterized by a decreased glomerular filtration rate (GFR), which can cause the breakdown of protein reserves, resulting in malnutrition. This study aimed to determine the mechanism underlying the relationship between decreased GFR and the risk of malnutrition in pre-dialysis CKD patients. Scoping review method using PubMed, ScienceDirect, and SpringerLink databases with the criteria of articles published from 2014 to 2024 and using RCTs or cross-sectional studies. Relevant articles were selected through the PRISMA method. The results showed that a decrease in GFR was strongly associated with malnutrition in pre-dialysis CKD through three main mechanisms: increased protein catabolism, decreased serum creatinine/cystatin C ratio, and increased number and diversity of drug prescriptions. Malnutrition due to changes in GFR can be observed through BMI, MUAC, muscle and fat mass, and handgrip strength. In conclusion, the lower the GFR, the higher the risk of malnutrition in pre-dialysis CKD and the lower the BMI value and MUAC size, reduced muscle mass and fat, and decreased handgrip strength and worsening kidney function, as indicated by the lower GFR.